Anti-inflammatory and anti-diarrheal effects of methanolic extracts of seeds and peel of Nephelium longan fruits in rats - Ripa, Farhana Alam; Habib, Afroza (© 2013 Iranian Journal of Pharmacology and Therapeutics, 2016)
This article was published in Iranian Journal of Pharmacology and Therapeutics [© 2013 Iranian Journal of Pharmacology and Therapeutics] and the definite version is available at: http://ijpt.iums.ac.ir/index.php/ijpt/article/view/1141/515 The article website is at: http://ijpt.iums.ac.ir/index.php/ijpt